Cultura del gusto e difesa del sapore: Per una ri-socializzazione dell’alimentazione - Spagna, Giovanni (Mediascapes journal, 2022)
This essay wants to analyze phenomenologies that influence food culture today and that, due to the consequent homologation imposed by globalization, would represent a dystopian element and anomic distortion. In particular, there would be a double influence on the individual in their manifestation, the effect of which would be the inevitable conditioning of the subjective ability/faculty to distinguish and choose. This influence could hypothetically be connected, firstly, to the products flavor loss spread out of season and, secondly, to the increasing daily rhythms, which very often prevent the preparation and consumption of healthy foods, forcing to resort to precooked foods or junk foods, to be consumed quickly perhaps, sacrifying quality, taste and sharing of the meal. Extremely, it could be said that taste has been transformed into a post-taste, reduced to a common and generalized universal denominator. The conclusions will concern the formulation of hypotheses that connect the considered topics, without failing to reflect on further points that will emerge during the work.